ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE STUDI EMPIRIS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2021 - Welsi Anggraini; Sulastiningsih Sulastiningsih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to analyze the prediction of bankruptcy using the Altman Z-Score method empirical studies on property and real estate companies listed on the indonesia stock exchange for the period 2012-2021. This type of research is quantitative descriptive research. The data used in this study is secondary data, where the data is obtained by accessing the idx.co.id site. In addition, data collection techniques were also carried out vy studying books, notes, journals, and related information. Sampling using purposive sampling with certain criteria, so that it can be determined 20 companies as samples in this study. The variables used in the financial ratios in the modified Altman Z-Score model are: working capital to total assets, retained earning to total assets, eraning before interest and taxes to total assets, and book value of equity to book value of total debt. The method used is the Altman Z-Score modified model because it can be used to predict company bankruptcy. The results showed that of the 20 companies there were 7 (seven) stable companies for (10) ten consecutive years with the code BAPA, BEST, BSDE, DUTI, GPRA, KIJA, MTLA. And there are 13 (thirteen) companies that have varied results, namely APLN, ASRI, CTRA, DART, DILD, EMDE, GMTD, JRPT, LPCK, LPKR, MDLN, PWON, and SMRA codes.